Life cycle impact assessment (LCIA) of potable water treatment process in malaysia: Comparison between dissolved air flotation (DAF) and ultrafiltration (UF) technology - Sharaai, Amir Hamzah; Mahmood, Noor Zalina; Sulaiman, Abdul Halim (American-Eurasian Network for Scientific Information, Jordan, 2009)
This Life Cycle Impact Assessment (LCIA) study compares two types of drinking water technologies; Dissolved Air Flotation (DAF) technology and Ultra Filtration technology. The selected plant for this study has both types of technologies in use. Collected data are from the usage of electricity and chemicals used in the water treatment process. The Eco-Indicator 99 was chosen to indicate extent of damage from collected inventories. From the result of impact assessment conducted, it is found that Ultrafiltration technology contributes higher impact to all three categories of damages; damage to environmental quality, damage to human health and damage to source when this technology is compared to DAF technology. Â© 2009, INSInet Publication.